Pengaruh Em, Size, Roe Dan Lev Terhadap Dpr Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Tahun 2014-2016 - Hastuti, Rini Tri (Jurnal Ekonomi, 2018)
The purpose of this research is to examine the effect ofearnings management, firm size, return on equity and dividend payoutratio on manufacturing companies listed in the Indonesian Stock Exchange in 2014-2016.The sample was determined by purposive sampling method. The research conducted by taking 117 manufacturing companies. The result of this research showed that earnings management and firm size have no significant effect on dividend payoutratio, while return on equity and leverage have significant effect on dividend payoutratio.